Mandi Marabit Menurut Majelis Ulama Indonesia Kabupaten Labuhanbatu Selatan - Siregar, Amiruddin; Iwan, Iwan (Postgraduate Program in Law, Pattimura University, 2024)
Introduction: The people of Aek Korsik village carry out Marabit bathing activities in the river because the majority of the people of Aek Korsik village do not have a well and those who do have a well sometimes feel water difficulties and the distance of their houses to the river is very close to travel. The community admitted that they did not cover all their awrah when bathing, and felt that it was natural that not all their awrah could be covered when they were in the riverPurposes of the Research: This study aims to describe the habits of the Aek Korsik people of Sungai Kanan District who practice bathing in one place in the river between men and women which is referred to as the Marabit bathMethods of the Research: This study aims to describe the habits of the Aek Korsik people of Sungai Kanan District who practice bathing in one place in the river between men and women which is referred to as the Marabit bath Results of the Research: The results of the study show that the habit of bathing in Marabit carried out by the people of Aek Korsik village is prohibited in Islam because it shows aurat. The reason for bathing in the river in the same place between men and women is because there is no well at home, there is often a lack of water, and this has been a habit of the people of Aek Korsik village since ancient times. If viewed from an Islamic point of view, that bathing in the river carried out by the people of Aek Korsik village and in general the river is passed by the community every day to carry out various activities is a very forbidden act, because it opens the awrah. While every Muslim and Muslim is obliged to cover the awrah, by covering the awrah can avoid committing adultery.